ASOSIASI CENDAWAN MIKORIZA ARBUSKULA (CMA) PADA KETAPANG (Terminalia catappa) - trus, Pe; hanuddin, Bur; Wulandari, Reine Suci (Universitas Tanjungpura, 2013)
Association observation of Arbuscular Mycorrhizal Fungus (AMF) was conduct in Sylviculture Forestry Faculty Laboratory of Tanjungpura University Pontianak. Soils sample and roots from plant Terminalia catappa which located in sea shore in Dusun Mawar, Sungai Itik Village, Sungai Kakap District, Kubu Raya Regency, Kalimantan Barat. The result of research was in Terminalia catappa plant found the base information that there are association between AMF with the plant, the result characteristic observation of spore type found 7 spore species, which are 6 species from Genus Glomus and 1 species from the Genus Gigaspora. Average of association level was take place in roots of Terminalia catappa plant including in class 2 and 3 it is low to moderate. Keywords : Association, AMF, Terminalia catappa.